1999
DOI: 10.1177/135676679900500306
|View full text |Cite
|
Sign up to set email alerts
|

Tourism destination brands and electronic commerce: Towards synergy?

Abstract: This paper discusses the impact of electronic commerce on the development of strong tourism destination brands. Electronic media have the potential to create strong direct links between individual tourism suppliers and their customers, thereby possibly undermining collective efforts to create strong destination brands. In addition, electronic media may have the potential to strengthen the process of destination brand creation, by facilitating interaction and cross-selling between complementary producers within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…Brand image is a key component in the formation of a clear and recognizable brand identity in the market (Williams et al, 1999). Due to the interrelationship between destination choice behavior and destination image, there is an increased interest in destination image as a predictor variable in the destination choice model.…”
Section: Image As a Pivot In Destination Positioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Brand image is a key component in the formation of a clear and recognizable brand identity in the market (Williams et al, 1999). Due to the interrelationship between destination choice behavior and destination image, there is an increased interest in destination image as a predictor variable in the destination choice model.…”
Section: Image As a Pivot In Destination Positioningmentioning
confidence: 99%
“…Electronic commerce has far reaching impact on the way travel is marketed, distributed, sold and delivered (Williams & Palmer, 1999;Pollack, 1995 Figures I & 2). The Internet has put consumers in control oftheir plans.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a number of researchers have noted the Internet's ability to marginalize the role of traditional travel agencies. Tyler (2000) and Williams (1999) said that traditional travel and tourism agencies need to restore their marketing activities and functions and take advantage of online services to achieve economies of scale without high new investments. The researchers also confirmed that the world of the Internet has created an opportunity for local and global virtual travel agencies such as Booking.com, Expedia.com, Travel.com, and Priceline.com, which have become able to compete in travel tourism by providing real value for both parties, the service providers and the clients.…”
Section: Internet In Saudi Arabiamentioning
confidence: 99%
“…Therefore, the rapid adoption of Internet marketing by hotels has yielded myriad studies of hospitality Internet adoption and its impact on hotel operation [3]. Many studies discussed the current stand of and potential role of internet in marketing and promoting tourism destinations [4][5][6][7][8]. This progress is also apparent in studies further considering hotel website dimensions and attributes and their effect on the perceptions of online browsers and purchasers, such as those of [9][10][11].…”
Section: Literature Review E-marketing In the Tourism And Hospitalitymentioning
confidence: 99%